Modern «philological novel» Discourse as an artistic experiment: Figl-Migl’s prose - Irina N. Ivanova (Актуальные проблемы филологии и педагогической лингвистики, 2021)
The article presents a certain way of modern transformation of the so-called “philological novel” in the modern Russian prose. The author asserts that this genre, which has a profound tradition and generally rests upon quite traditional philological gnoseology and axiology, has changed significantly since, e.g., “Pushkin’s house” by A. Bitov, and the reason for this change is radical transformation of basic concepts of artistic discourse. The status of fine literature and its social functioning, the issue of Author and his/her dialogue with the Reader, the very nature of a word, especially a “foreign” one, have changed. Modern literature does not pretend to be didactical anymore, as it had in a sense been in classical paradigm of the Author/Reader relationship, and it is gradually transforming into an intellectual game with ready-made linguistic and ideological constructs. The purpose of the article is to study the ways modern artistic discourse of Figl’-Migl’s “philological novel” transforms. The research rationale is explained by the absence of scientific works, dedicated to the specific discourse of such novels, in the modern Russian theory and history of literature. The author considers that Figl’-Migl’s prose is distinguished by universal ironization of the total intertextuality, that is common for postmodernism; by principal tendency for the absence of anyone’s “own” word at all, and by the author’s and the protagonist’s reluctance to associate themselves with any distinctly identifiable axiological and ideological system, including the “love for word”. Artistic discourse of Figl’-Migl’s novels may be considered experimental, since the author, by imitating various types of “foreign” discourse, playing with them and bringing together characters, absolutely unimaginable within one and the same dialogue, as discourse carriers, puts them in contexts, unusual for them and for the reader, but virtually modelled by the whole history of the Russian literature, which is present in the novels as a background and a full participant of the dialogue’s events.